The Influence of Service Quality and Claimant Satisfaction on the Corporate Image of PT Jasa Raharja, North Sumatra Branch - Naimi Yumna Sinurat; Mesra B (Yayasan Multidimensi Kreatif, 2024)
The research analysis aims to determine whether service quality partially has a positive and significant effect on the corporate image of PT Jasa Raharja, North Sumatra Branch. Whether claimant satisfaction partially has a positive and significant effect on the corporate image of PT Jasa Raharja, North Sumatra Branch. Whether service quality and claimant satisfaction simultaneously have a positive and significant effect on the corporate image of PT Jasa Raharja, North Sumatra Branch. The data analysis technique used is the associative quantitative research method with the help of the SPSS program. This study uses multiple linear regression. The sample in this study was 82 respondents. Primary data collection using a questionnaire. The results of the study indicate that service quality partially has a positive and significant effect on the corporate image of PT Jasa Raharja, North Sumatra Branch. Claimant satisfaction partially has a positive and significant effect on the corporate image of PT Jasa Raharja, North Sumatra Branch. Service quality and claimant satisfaction simultaneously have a positive and significant effect on the corporate image of PT Jasa Raharja, North Sumatra Branch.